The little reindeer - Killen, Nicola (New York : Simon & Schuster Books for Young Readers, 2017)
"When a jingling sound wakes her from her sleep, a little girl's dreams come true when she meets a lost reindeer in the forest. They set off on a magical adventure and it becomes a Christmas never to forget"--
"A Paula Wiseman book."
Originally published: London : Frances Lincoln Publishers Ltd, 2016 under the title Ollie's Christmas reindeer.
Keywords: Adventure and adventurers -- Fiction; Reindeer -- Fiction; Christmas -- Fiction; JUVENILE FICTION / Holidays & Celebrations / Christmas & Advent; JUVENILE FICTION / Religious / Christian / Holidays & Celebrations; JUVENILE FICTION / Fantasy & Magic